PENGARUH KEPEMILIKAN INSTITUSIONAL DAN PENGUNGKAPAN TATA KELOLA PERUSAHAAN TERHADAP AGRESIVITAS PAJAK - Birgitta Evangeline Rennath; Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine the effect of institutional ownership and disclosure of governance on tax aggressiveness with tax avoidance as a moderating variable in food manufacturing companies listed on the IDX. Tax aggressiveness is the dependent variable, while institutional ownership and corporate governance disclosure are independent variables. The data used are secondary data and samples are financial reports and annual reports from 29 companies listed on the IDX in 2013-2019. This study uses a non-randomized method. The sample selection technique used purposive sampling and the data were analyzed using the inner and outer model analysis. Data were analyzed using SPSS software version 23 and Smart PLS version 3.2.2. The results showed that institutional ownership variables did not have a significant effect on tax aggressiveness and institutional ownership and firm size had no significant effect on tax aggressiveness. To get better research results, further research can add other variables that have a big possibility of influence, use companies other than manufacturing, and extend the research period.